Analisis Strategi Bauran Pemasaran Pada PT Amita Mandiri Cabang Setu Bekasi - Kintan Riyani Akhla; Diana Prihadini; Ridfa Chairani (JAMBIS : Jurnal Administrasi Bisnis, 2022)
This study was conducted to analyze the marketing mix strategy of goods at PT Amita Mandiri Setu Bekasi Branch. The method used was descriptive qualitative with the data collection techniques of observation, interviews, and documentation. Based on the results of the analysis, it is concluded that PT Amita Mandiri, Setu Bekasi Branch, combines elements in marketing that are emphasized on the 4Ps. The product of PT Amita Mandiri Branch Setu Bekasi is bottled drinking water of various sizes and brands. The price offered is affordable for retailers, semi wholesalers with the place in a strategic location on the side of the road. Promotion is carried out directly by word of mouth, and personal selling. PT Amita Mandiri Setu Bekasi Branch also implements STP (segmenting, targeting, positioning) judging from determining the offer, and understanding the needs and interests of customers. In setting a target market, it can be seen from the company evaluating market segments, selecting market segments, and being able to generate customer value, the positioning is from planning a position that can differentiate products from other products but in reality, there is no difference. This is because the company sells the same product as competitors' products. This strategy has succeeded in increasing sales volume, as evidenced by sales volume data in March-April 2022.